Country Practice (Part 4) - Memoirs of the late Dr. DH Girdwood (Bedford, Eastern Cape) - Ian Couper (South African Family Practice)
The RHI presents the reflections of a rural GP, the late Dr DH Girdwood, written in his retirement a few years ago. Dr. DH Girdwood was a general practitioner who had his practice in Bedford, Eastern Cape, from 1949 until he retired in 1983. He passed away in July 2001 and permission to publish these memoirs was obtained from his son, Dr. AH Girdwood, who is a gastroenterologist practising in Pinelands. It provides a fascinating account of the experiences of a rural doctor in the South African context. These reflections have been artificially divided into 4 parts. We welcome similar reflections on past experiences from other readers.